ELAS, NÓS, EU (ENTRE PROFESSORES QUE ENSINAM MATEMÁTICA): episódios de uma formação. - Susilene Garcia da Silva Oliveira (2022)
In this research I seek to investigate a group of teachers from the early years who teach mathematics in public schools in the city of Aquidauana MS. The objective is to describe and discuss the meetings that took place between 2015 and 2018. In view of what was being produced from the narrations of the episodes of these meetings, I chose the anthropological theory of the didactic (TAD) and some of its assumptions, among them the co-determination levels and topogenesis. The stories of the teachers intertwined with those of many other subjects constituted this thesis. We seek to answer some questions: How do institutions influence whether or not to stay in training groups? What are the conditions and restrictions that can be identified and analyzed regarding this permanence? We found in TAD a theory based on notions and elements that manage to cover several phenomena that happen in the process of composition and maintenance of a formation group. In addition, we were able to reveal how the levels of didactic co-determination influence various actions of these teachers and contribute significantly to the research. In the field of Didactics of Mathematics, we offer a study result that allows several new investigations from what is described and discussed about institutions, personal relationships, subjection, institutional relationships. But this research mainly reports the context of teachers who teach mathematics their afflictions and achievements during this continuous process that is teaching and learning.